Sales and Marketing Strategies Duck Nugget Product Using Porter’s Five Force and SWOT Analysis - Fathul Amal Syamsul Arifin; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Journal of Multidisciplinary Academic, 2019)
The population rate in Indonesia is goes up every year and it affects the growth of food industry in Indonesia which is developed gradually every year. Here, a food industry produces various products like cooked food, processed food in a form of frozen food. For frozen food, it has its own target market and the number is bigger than the market of cooked food due to its durable characteristic and cooking friendly. The growth of the frozen food sales in Indonesian market is a business opportunity for PT. BEFINDO FOOD. Therefore, PT. BEFINDO FOOD focuses on frozen food industry by using manufactured duck as its main ingredients it’s different by other companies. In this study, we use Porter’s Five Forces analysis method and SWOT analysis to investigate any factual information that needs to be taken into consideration, which is related to the frozen food business. The result shows, growth of the frozen food sales in the market is expected to be the business opportunity for PT. BEFINDO FOOD to produce a nugget with manufactured duck as its main ingredients. It aims to reach wider market to offer alternative flavor of nugget product.